A DNA-based real-time PCR assay for robust growth quantification of the bacterial pathogen Pseudomonas syringae on Arabidopsis thaliana. Issue 1 (December 2016) - Ross, Annegret; Somssich, Imre
Abstract Background The interaction ofPseudomonas syringae with Arabidopsis is one of the most commonly used systems to study various bacterial—host interrelationships. Currently, most studies are based on the growth quantification of the pathogen to characterize resistance or virulence targets. However, the standard available method for determining bacterial proliferation in planta is laborious and has several limitations. Results Here we present an alternative robust approach, which is based on the quantification of bacterial DNA by real-time PCR. We directly compared this assay with the routinely used plate counting method to access bacterial titers in a number of well described Arabidopsis mutants. Conclusions These studies showed that the DNA-based technique is highly reliable and comparable. Moreover, the technique is easily applicable, robust, and ideal for routine experiments or for larger scale analyses.